2012
DOI: 10.1001/archoto.2011.1199
|View full text |Cite
|
Sign up to set email alerts
|

Transoral Robotic Surgery Using the Thulium:YAG Laser<subtitle>A Prospective Study</subtitle>

Abstract: Compared with EC:TORS, TY:TORS seems feasible and safe. In addition, TY:TORS resulted in fewer intraoperative pharyngotomies and less postoperative pain than did EC:TORS, which may be because of decreased collateral thermal damage, improved visualization, and finer cutting using the thulium laser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 20 publications
4
23
2
Order By: Relevance
“…Rates of perioperative feeding tube placement varied widely by disease stage and institutional practices (3% to 100%), and the average duration of perioperative nasogastric tubes was 2 to 13 days. 11,13,17,18 Excluding prophylactic placement, 15 18% to 39% of patients required gastrostomy placement, typically during adjuvant therapy. A single study of radical tonsillectomy reported the placement of gastrostomy tubes intraoperatively in all patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Rates of perioperative feeding tube placement varied widely by disease stage and institutional practices (3% to 100%), and the average duration of perioperative nasogastric tubes was 2 to 13 days. 11,13,17,18 Excluding prophylactic placement, 15 18% to 39% of patients required gastrostomy placement, typically during adjuvant therapy. A single study of radical tonsillectomy reported the placement of gastrostomy tubes intraoperatively in all patients.…”
Section: Resultsmentioning
confidence: 99%
“…Excluding studies that restricted inclusion to early stage disease and those that routinely prophylactically placed PEG tubes, 18% to 39% required PEG tubes in TORS series 1113,16,1819 compared with 29% to 60% of patients in definitive IMRT series 6,2025 (Figure 2). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The surgeon is provided with an endoscopically derived three-dimensional visual display that is colocated with control handles that direct movements of the robot's instruments inside the patient's body. Standard surgical instruments, including tissue forceps, a spatulated electrocautery device, or carbon dioxide 20 and thulium laser, 21 are then used to perform an en bloc resection of the oropharyngeal tumor. A bedside assistant provides countertraction and suction while caring for the patient throughout the procedure (Fig 3).…”
Section: Torsmentioning
confidence: 99%